1999 : Victory Without War - Nixon, Richard (GHQ, Rawalpindi Army Education Press, 1988)
In this acclaimed national best-seller, Richard Nixon offers a comprehensive strategy for the West - a vital plan of action that will help ensure peace, prosperity, and freedom in the next century. From glasnost and summitry to arms control and "Star Wars," from Nicaragua and China to Europe and Japan, he gives seasoned, no-nonsense advice on all tough foreign policy issues. The former president draws on a lifetime of experience in international affairs to examine the crucial challenges facing the United States and the West and how best to go forward in the 21st century. "Nixon raises all the timely questions about the present state of the world, and then answers them both systematically and thoroughly."
Include Index
An analysis by Richard Nixon as commentator on world affairs, arguing that Soviet aims have not changed under Gorbachev, presenting his view of what future Western strategy should be. He also examines the future prospects of Western Europe, Japan, China and the Third World.
Keywords: United States -- World politics -- Diplomatic relations -- Strategy